Analisis Nilai Religius pada Novel Cinta dalam Ikhlas Karya Abay Adhitya serta Pemanfaatanya sebagai Bahan Pembelajaran Bahasa dan Sastra Indonesia di SMA Kelas XI - Maulana, Nanang (Universitas Mathla'ul Anwar Banten, 2020)
This study has a background, among others, a decline in religious values which has an impact on the morals and morals of students. This study aims to describe: (1) religious values, (2) and its use as learning materials for Indonesian language and literature in class XI SMA. The method used in this research is descriptive method. The object of research is the novel “Cinta dalam Ikhlas” by Abay Adhitya”. The object of research is the religious value of the novel “Cinta dalam Ikhlas” by Abay Adhitya and its use as a learning material for Indonesian language and literature in XI grade high school. The technique used in this research is the library technique, reading and taking notes. The research instrument was the researcher recording the data in the novel of “Cinta dalam Ikhlas” by Abay Adhitya and books for writing references. The data analysis technique, the writer chose content analysis technique. The technique of presenting the results of data analysis used informal techniques. The results of this study can be concluded that (1) religious values include (a) human relations with God, (b) human relations with humans, (c) human relationships with oneself. (2) and its use as learning materials for Indonesian language and literature in XI grade SMA. Learning is carried out using the 2013 curriculum reference, KD 3.20 to analyze the messages from the two fiction books that are read.